021 Emergency department hypertension, is it real? A systematic review and meta-analysis. Issue 12 (21st November 2019) - Reynard, Charles; Oliver, Govind; Berg, Patricia van den; Naguib, Mina; Body, Richard
Abstract : Background: In 2017 15, 379, 166 patients attended emergency departments (ED) across the U.K. Attention is focussed on how EDs are struggling to cope with rising demand. However, each attendance presents an ideal screening opportunity for the nation's second largest cause of avoidable mortality; cardiovascular disease. We sought to evaluate a common cardiovascular prognostic factor measured in the ED. We aimed to conduct a systematic review of the prevalence and reliability of ED hypertensive readings. Method and results: The review was conducted in accordance with the PRISMA and was registered on PROSPERO. We planned to conduct a meta-analysis if the data was suitable. Searches were conducted using pre-determined terms using MEDLINE and Embase databases. A hand search of the grey literature was also conducted. Studies eligible for inclusion were those: peer reviewed, conducted in the last 20 years, included a general population, and written in English. Risk of Bias was assessed by the QUIPS tool, and overall quality by GRADE. Searches, screening, data extraction, risk of bias and GRADE assessment were all conducted by two independent researchers. Conclusions: The search identified 1, 071 results, after title and abstract review 47 underwent full text review. A further 26 were excluded following full text review (table 1 ). The outcome of prevalence was extracted from 13 studies. They were dominated numerically by McNaughton et al 's study of 701, 952, 422 patients, with the next largest having 7, 238. A meta-analysis was conducted and confirmed the prevalence finding of the largest study at 0.24 (95% CI 0.02–0.45) (see figure 1 ). The persistence at follow of hypertensive ED readings was extracted from 7 studies, a random effects model was conducted demonstrating a pooled persistence of 0.55 (95% CI 0.34–0.75) (see figure 2 ). Hypertension is common and the persistence of it at follow up adds credibility to ED's public health potential.